Review of the Constitutional Court's Decision Number: 82/PUU-XII/2014 on Women's Representation in Parliament in the Perspective of Legal Feminism - Fitriana, Alisa Zahra; Muslim, Ikhwanul; Yulianingrum, Aullia Vivi (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: This study analyzes the Constitutional Court Decision Number: 82/PUU-XII/2014 which is a critical basis and an important basis for resolving the problem of women's representation in legislative institutions. Despite various legal provisions ensuring women's representation, challenges in practical implementation persist.Purposes of the Research: The research aims to examine the Constitutional Court's reasoning on the concept of women's representation and assess the consistency of equality principles through the lens of legal feminism.Methods of the Research: This study employs a normative juridical research method with a descriptive approach, focusing on the judicial interpretation of women's representation and its impact on affirmative policies in politics.Findings of the Research: The findings reveal that Decision Number: 82/PUU-XII/2014 reflects efforts to protect women's constitutional rights by reinforcing the phrase "prioritizing women's representation," despite its lack of explicit regulation. The study also indicates that the Constitutional Court consistently applies legal feminism principles to ensure equal opportunities in legislative institutions. However, the repeal of gender affirmative measures in Law Number: 17 of 2014 on MD3 has led to legal uncertainty, disadvantaging women.